Information communication technologies concepts, methodologies, tools and applications - Van Slyke, Craig; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This collection meets these research challenges; compiling breaking research in the pivotal areas of social adaptation to information technology. It covers ad-hoc networks, collaborative environments, e-governance, and urban information systems, case studies, empirical analysis, and conceptual models. Over 300 chapters contributed by experts, this six-volume compendium will provide any library's collection with the definitive reference on ICTs"--Provided by publisher.
Fundamental concepts and theories in information communication technologies -- Information communication technologies development and design methodologies -- Information communication technologies tools and technologies -- Utilization and application of information communication technologies -- Organizational and social implications of information communication technologies -- Managerial impact of information communication technologies -- Critical issues in information communication technologies -- Emerging trends in information communication technologies.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 22, 2010).
Keywords: Information technology -- Social aspects; Information technology -- Economic aspects; Information technology -- Political aspects; Digital communications -- Social aspects; Information society; Adaptive ICT-Based Learning Environment; Computing and ICT Literacy; Convergence of ICT and Culture; Cultural Studies Approach to Gender and ICT; Developing Regional Tourism Using ICT; Enabling Strategy Formulation by ICT; Gender and ICT Policy; ICT and Business in the New Economy; ICT and Developing Social Capital; ICT and Knowledge Management Systems; ICT and the Efficient Markets Hypothesis; ICT and the Travel Industry; ICT Applications in Aviation; ICT in Regional Development; ICT, Work Organizations, and Society; ICT-Based Learning; ICTs as Tools for Poverty Reduction; ICTs for Intercultural Dialog; Impact of ICTs on Learning Agency; Integrating ICT in Universities; Mobile ICT; New ICTs for Conflict Prevention and Management; Patents and Standards in the ICT Sector; Political Uses of ICT Initiatives; Transforming Democracy through ICT; Electronic books